2010
DOI: 10.3109/0142159x.2010.509412
|View full text |Cite
|
Sign up to set email alerts
|

A blended approach to invasive bedside procedural instruction

Abstract: A blended, standardized curriculum in invasive bedside procedural instruction can significantly improve performance in participants' medical knowledge and technical skills.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
40
0
4

Year Published

2010
2010
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 48 publications
(45 citation statements)
references
References 15 publications
1
40
0
4
Order By: Relevance
“…The perceptions of the survey respondents presented here support these findings. Furthermore, instructional videos have been shown to be effective in teaching clinical skills like bedside procedures or resuscitation algorithms, either provided in classic fashion (Braslow et al, 1997;Carrero et al, 2009;Lenchus et al, 2011;Todd et al, 1998), or interactively embedded in virtual environments (de Vries and Handley, 2007;Lehmann et al, 2015;Ventre et al, 2011). As the participants in this survey underlined, constructive alignment with corresponding teaching activities is the key to successful implementation of learning activities (Biggs and Tang, 2007).…”
Section: Findings and Implications For Educational Practicementioning
confidence: 90%
“…The perceptions of the survey respondents presented here support these findings. Furthermore, instructional videos have been shown to be effective in teaching clinical skills like bedside procedures or resuscitation algorithms, either provided in classic fashion (Braslow et al, 1997;Carrero et al, 2009;Lenchus et al, 2011;Todd et al, 1998), or interactively embedded in virtual environments (de Vries and Handley, 2007;Lehmann et al, 2015;Ventre et al, 2011). As the participants in this survey underlined, constructive alignment with corresponding teaching activities is the key to successful implementation of learning activities (Biggs and Tang, 2007).…”
Section: Findings and Implications For Educational Practicementioning
confidence: 90%
“…27 Our study evaluated the effect of simulation-based education with mastery learning for resident education using rigorous assessment standards. Earlier studies used simulation to evaluate LP skills of internal medicine, 28 emergency medicine, 29 and pediatric residents, 30 but mastery standards were not imposed. Use of the mastery model improves clinical care in advanced cardiac life support 13 and central venous catheter insertion.…”
Section: Resultsmentioning
confidence: 99%
“…Five studies were identified [13, 16, 21-23]. All studies provided assessment tools for assessing competence in thoracentesis, though three of them focused on needle thoracentesis [13, 21, 22]. Two studies provided assessment tools for TPCT, but they used the Seldinger technique when inserting the catheter [16, 23].…”
Section: Methodsmentioning
confidence: 99%